A good bad boy : Luke Perry and how a generation grew up - Wappler, Margaret (New York : Simon & Schuster, 2024)
Best known for playing loner rebel Dylan McKay in Beverly Hills 90210, Luke Perry was fifty-two years old when he died of a stroke in 2019. There have been other deaths of 90's stars, but this one hit different. Gen X was reminded of their own inescapable mortality, and robbed of an exciting career resurgence for one of their most cherished icons, with recent roles in the hit series Riverdale and Quentin Tarantino's Once Upon a Time In Hollywood bringing him renewed attention and acclaim. Only upon his death, as stories poured out online about his authenticity and kindness, did it become clear how little was known about the exceedingly humble actor and how deeply he impacted popular culture. Here, Margaret Wappler attempts to understand who Perry was and why he was unique among his Hollywood peers.
Includes bibliographical references.
Keywords: Perry, Luke, -- 1966-2019.; Actors -- United States -- Biography; Biographies